Cytotoxic chemotherapy: clinical aspects. (February 2020) - Jones, Rob; Ocen, Joanita
Abstract: Chemotherapeutic drugs exert their effects by interfering with the processes involved in cell division. Their therapeutic use stems from their ability to cause a greater proportion of cell kill in cancer cells than normal cells. In this review we discuss the clinical uses of chemotherapeutic agents, their mechanisms of action, important toxicities and patterns of resistance.